Take My Breath Away: Competing Contexts Between Domestic Violence, Kink and The Criminal Justice System in R. v. J.A. - Khan, Ummni (Oñati Socio-Legal Series, 2016)
In the R. v. J.A. case, a man was criminally convicted for performing sexual activities on his partner while she was rendered unconscious through erotic asphyxiation. Evaluating the legal and ethical stakes of the case is challenging because the complainant changed her testimony from non-consent to consent at trial, and the couple’s history includes both kinky sex and domestic violence. In this paper, I problematize the legal reasoning of the trial judgment (R. v .A.(J.) 2008 ONCJ 195), the Supreme Court of Canada’s majority decision ([2011] 2 S.C.R. 440), as well as the LEAF factum, and some of the feminist commentary. I argue that both the legal and the feminist discourses privilege domestic and sexual violence as the preeminent context in this case, erase or gloss over kinky eroticism and subjectivity, and advance a carceral politics that privileges the criminal justice system as an articulator of truth, and a vehicle for gender justice.